Common Fixed Point of Mappings Satisfying Rational Inequalities in Complete Complex Valued Generalized Banach Spaces - Rakesh Kumar Jaiswal, Arihant Jain (Mathematical Statistician and Engineering Applications, 2021)
In the present paper we have defined the concept of complex valued generalized Banach spaces. Some common fixed-point theorems involving rational inequalities have been proved. We also prove work periodic point property of common fixed-point problem for two rational type contractive mappings.